POTENSI DAN STRATEGI PENGEMBANGAN PARIWISATA DI KAWASAN DISTRIK ARURI KABUPATEN SUPIORI - Mandosir, Marthen Luther; Rante, Harmonis; Numberi, Jonathan (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2023)
One source of foreign exchange for an area and a source of income for local communities is to develop the natural potential in the area as a tourist attraction according to its natural conditions. The potential of natural resources certainly requires different development strategies according to their potential with the support of local resources based on the local wisdom of an area. The reality that is happening in the Aruri Islands District, Supiori Regency at this time is that the district consists of a group of islands that have tourist attractions, especially coastal nature tourism, cultural tourism, underwater tourism and marine tourism. The tourism potential in this area is very promising, but it is hampered by problems of access and government capital in developing its tourism potential. So it requires a breakthrough in the field of tourism that can boost sources of income for the community. In conducting this research, the method used is a qualitative descriptive method to assess the potential, tourism development strategies carried out by the Tourism Office in Aruri District, Supiori Regency. The results show that there is potential for natural tourism, and cultural tourism and underwater tourism that have not been managed optimally by the local government. The three types of tourism potential are closely related to migration between residents on Biak and Supiori islands in the 17th and 18th centuries and in the early 19th century and the events of the first and second World Wars. A special approach is needed in exploring the potential of local nature and culture in order to earn foreign exchange through tourism development in the area.